Analyzing the predictive capacity of various machine learning algorithms - Mathew Biju, Soly (International Journal of Engineering and Technology, 2018)
The purpose of this study is to deploy and evaluate the performance of the new age machine learning algorithms and their applicability in business environment. Three unique set of datasheets were used to evaluate the true performance of top 4 machine learning algorithms â€“ i.e. Generalized Linear Models (GLM), Support Vector Machine (SVM), K-nearest neighbor (KNN) and Random Forests. The findings of this study revealed that although these algorithms take different way of solving classification and regression problems, they develop quite robust models by understanding and learning the hidden patterns in the datasets. The findings of this study can be used by other companies and individuals while analyzing and solving their respective business problems. Although a number of studies exist where new-age machine learning algorithms are tested and evaluated, there are none where the performance of these algorithms was tested on different size and type of datasets.Â Â